The genetic characterization of germplasm and identification of the litter size trait associated candidate genes in Dexin mutton and fine-wool sheep - Zhu, Mengting; Li, Pengfei; Wu, Weiwei; Zheng, Wenxin; Huang, Juncheng; Tulafu, Hanikzi; Lin, Changchun; Tao, Weikun; Aladaer, Qi (Frontiers in Genetics, 2024)
Xinjiang is a major province of sheep breeding in China, which plays an important role in meeting people's needs for meat products, increasing farmers' income and sustainable development of animal husbandry. However, the genetic differentiation relationship between breeds was not clear, and most sheep had low fecundity, which seriously restricted the efficient development of sheep industry. Therefore, this study used the whole genome resequencing to detect the genetic variation of Dexin mutton & fine-wool sheep, explored the selected regions and important genes of the litter size traits, analyzed the genetic mechanism of reproductive traits, and provided new insights for the high fecundity breeding of sheep. A total of 5,236.338 G genome data and 35,884,037 SNPs were obtained. Furthermore, we identified 39 selection signals spanning candidate genes, 99 genes were significantly associated related to growth, reproduction and immunity, among which, BRIP1, BMPR1B, BMP4, NGF etc. genes, and MAKP signaling pathway, Fanconi anemia pathway and Thyroid hormone signaling pathway and other signaling pathways were significantly correlated with litter size trait. Among them, we identified NGF, TrKA and BRIP1 genes was the important genes for sheep litter size traits and the mutation frequencies of 9 SNPs in BRIP1 gene were significantly different in domestic sheep in the world. The research provided new insights for the breeding of self-cultivated meat fine-wool sheep.